A PRELIMINARY STUDY ON ENGLISH GRAMMAR PROFICIENCY KNOWLEDGE OF DIPLOMA STUDENTS - Ngo Kea Leng; Juliana Mohd Nor; Norhamimah Rani; Salihah Abdullah (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
The aims of the study were to determine the most frequent grammatical errors made by students and their performance in a grammar test. Hence,183 diploma students from a local university were chosen to assist in this study. The instrument of the study was a final test consisting of two reading comprehension passages and a grammar section. For the purpose of the study, the students’ answers of the grammar section were analysed. The grammar section consists of 10 questions covering different parts of speech and tenses which were randomly chosen. It was found that the majority of the students’ performance in a grammar test is in the middle range. Most of them did not perform badly but neither did most of them excel at English grammar. Based on the findings there seemed to be a need for a more enhanced focus on the teaching and learning of English grammar for Malaysian ESL students. However, because this is a small study that examined only one batch of students, the results of this study may not be too significant for a more generalised conclusion. Thus, continuous study should be done with regard to aspects of grammar knowledge and its teaching and learning in Malaysia.